Designing A Doppler Effect Experiment Using Smartphone Sound Sensor - Asep Akmal Fadia Nurhalim; Rahma Alliya Aqquilla; Najmi Hiyan Fathinah; Rizki Zakwandi; Alfiansah Sandian Prakoso; Ika Mustika Sari (Jurnal Teori dan Aplikasi Fisika, 2025)
This study explores the design of a Doppler effect experiment using a sound sensor on a smartphone. The main objective is to demonstrate that the change in sound frequency due to the relative motion between the source and the observer can be observed and measured using an easily accessible experimental setup. The experiment was conducted using a smartphone equipped with a sound sensor application to record frequency shifts from a moving sound source. The setup consists of a sound emitter with a constant frequency and either a moving observer or a moving source, making it easy to implement in educational settings. The results indicate that this experiment can effectively detect frequency changes. Data analysis shows an error rate ranging from 3.69% to 3.92%, proving that this method is sufficiently accurate for studying the Doppler effect. These findings highlight that integrating mobile technology into scientific experiments can be a valuable tool for educators, particularly in explaining wave phenomena such as the Doppler effect. Keywords: Doppler Effect, Physics Experiments, Educational Technology